Prospek Game Edukasi Dalam Pembelajaran Biologi - Hasyri, Yulia Rezki Nanda; Hajar, Ibnu (Al-AHYA: Jurnal Pendidikan Biologi, 2025)
This study aims to explore the prospects of using educational games in biology learning. The research method employed is descriptive with a quantitative approach. Data were collected using a Guttman scale questionnaire with "Yes" and "No" answer options. The population of this study consists of all 10th-grade students at SMAN 11 Pekanbaru, with a sample of 51 students selected through purposive sampling. The results indicate that the use of educational games has a positive impact on biology learning. The first indicator, the intensity of using educational games, revealed that 50% of respondents provided positive responses (sufficient). The second indicator, reasons for using educational games, showed 75% positive responses (good), including ease of understanding materials, increased interest, and learning motivation. The third indicator, benefits of using educational games, demonstrated 86% positive responses (very good), such as improved communication between teachers and students and enhanced learning efficiency. Overall, the use of educational games in biology learning achieved an average score of 70% with a "good" interpretation. These findings suggest that educational games as a learning medium can improve conceptual understanding, motivation, and students' interest in learning in a more engaging and interactive environment.